2017
DOI: 10.1017/apr.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Optimal portfolio selection under vanishing fixed transaction costs

Abstract: In this paper, asymptotic results in a long-term growth rate portfolio optimization model under both fixed and proportional transaction costs are obtained.More precisely, the convergence of the model when the fixed costs tend to zero is investigated. A suitable limit model with purely proportional costs is introduced and the convergence of optimal boundaries, asymptotic growth rates, and optimal risky fraction processes is rigorously proved. The results are based on an in-depth analysis of the convergence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…(18)) that H • ; c, x c , xc satisfies the second item above; moreover, H • ; c, x c , xc satisfies the first item above (with x c = y and xc = ȳ) within Case (i) (of Proposition 3.1). Hence, (21) holds in Case (i). It can be similarly shown that (21) holds in Case (ii).…”
Section: Appendix a Model Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…(18)) that H • ; c, x c , xc satisfies the second item above; moreover, H • ; c, x c , xc satisfies the first item above (with x c = y and xc = ȳ) within Case (i) (of Proposition 3.1). Hence, (21) holds in Case (i). It can be similarly shown that (21) holds in Case (ii).…”
Section: Appendix a Model Discussionmentioning
confidence: 92%
“…Remark 3.5. The properties (21) and (22) are established in [41, p. 675] in a setting similar to that of the present paper. The property (23) is established in [33,Remark 2] for a model based on a Wiener process with drift.…”
Section: Precommitment Solutionmentioning
confidence: 94%
See 1 more Smart Citation
“…To the best of our knowledge, such an analysis has not been carried out for exactly the optimal dividend problem (3.2). However, slightly different problems without absorption are studied in [34], and the references therein, and it is investigated what happens when the fixed cost c is sent to zero, see also [2,18,35]. One main finding is that while the value of the problem converges to the one without fixed costs as c ց 0 (as in Proposition 3.2) the derivative with respect to c converges to −∞.…”
Section: Sensitivity With Respect To K and Cmentioning
confidence: 99%
“…This kind of cost functional is also important in mathematics of finance under the name of Kelly criterion -see [16]. In particular impulse control appear in the case of growth optimal portfolio under proportional transaction costs in [10] and [7] and references there in. Average cost per unit time impulse control in a general (locally compact separable) state space was considered in [21].…”
mentioning
confidence: 99%